Analysis and measurement of vibration characteristics of a hollowing defect based on a laser self-mixing interferometer - Chen, Yu-Xin; Chen, Jin-Bo; Cao, Peng; Zhao, You-Guang; Wang, Jun; Teng, Xu-Wei; Wang, Chi (Chinese physics B, 2024)
To solve the problems with the existing methods for detecting hollowing defects, such as inconvenient operation, low efficiency and intense subjectivity, and to improve the efficiency of the acoustic-optic fusion method for detecting hollowing defects, in this paper the vibration characteristics of hollowing defects are measured and analyzed using a laser self-mixing interferometer. The ceramic tile above the hollowing defect is equivalent to a thin circular plate with peripheral fixed support. According to Kirchhoff’s classical circular plate theory and the circular plate displacement function based on the improved Fourier series, a theoretical model of a circular plate is established. By solving the characteristic equation, the theoretical modal parameters of hollowing defects are obtained. Subsequently, an experimental system based on a laser self-mixing interferometer is built, and modal experiments are carried out using the hammering method. The experimental modal parameters are obtained with a professional modal analysis software. Through comparative analysis between the theoretical and experimental modal parameters, the error of the natural frequency results is found to be tiny and the mode shapes are consistent. These results provide theoretical guidance for a practical non-destructive acoustic-optic fusion method for detecting hollowing defects.